Golay complementary codes, double pulse repetition frequency transmission - Igor Trots; Andrzej Nowicki; Marcin Lewandowski; Jerzy Litniewski; Wojciech Secomski (Archives of Acoustics)
This study concerns the development and investigation of a new composing method of short coded sequences and their transmission based on well-known Golay complementary codes and applied compression technique allowing to increase the signal-to-noise ratio (SNR) and penetration. This new method can potentially play important role in examination of superficial structures, e.g. dermatology, ophthalmology, etc. This paper reports the results of examination of the two pairs 3.5 MHz coded sequences of the same duration: the single 32-bits pair Golay sequences and combined sequences consisting of two 16-bits Golay codes separated in time. The results clearly demonstrate the potential of the combined coded transmission obtaining the SNR = 22.6 dB that is 2.6 dB higher than for the traditional Golay sequences and it is in case when coded length is two times shorter. For obtaining the same SNR using traditional method the code length should be at least 64 bits long, resulting in the increased dead zone up to 1.4 cm.